UK markups and profit margins during the pandemic and its aftermath - Alexander Guschanski; Özlem Onaran (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2025)
We analyse UK markups and profit margins for the pandemic period and its aftermath using unconsolidated balance sheets of non-financial corporations for both listed and unlisted firms. The markup increases by 14.7% between 2014 and 2022, exceeding any previously documented growth rate for UK markups, despite major economic, ecological and geo-political crises. The rise in markups is driven by both increasing markups within UK companies and a reallocation of output towards high-markup firms. However, the within effect has dominated since 2020, driven by large firms. In this regard, the UK is different from the US, where the reallocation effect has been more prominent. Since 2014, the markup distribution of firms has become more polarised. Increasingly more firms are at risk of financial difficulties due to low profit margins while at the same time some firms are charging historically extraordinarily high markups and reap high profits. This contributes to bankruptcy risk and economic instability while exacerbating pricing power for some companies. Preventing markup increases during macroeconomic shocks should be a priority for policymakers seeking to reduce inflationary pressure and adverse effects on income inequality.
Keywords: D4; J3; L1; 330; markup; profit margin; market power